Express each of the following in standard form y= 1/4x - 1/3 -4(-1/4x + y +1/3)=(0)-4 -3(1x - 4y -4/3)=(0)-3 -3x+12y+4=0 -3x+12y=-4 The answer is 3x-12y=4 I don't know what I did wrong, please help.
Follow Math Help Forum on Facebook and Google+
Originally Posted by buck Express each of the following in standard form y= 1/4x - 1/3 -4(-1/4x + y +1/3)=(0)-4 -3(1x - 4y -4/3)=(0)-3 -3x+12y+4=0 -3x+12y=-4 The answer is 3x-12y=4 I don't know what I did wrong, please help. Your ansswer is correct You have $\displaystyle -3x+12y=-4$ so, $\displaystyle -(3x-12y) = -4 \implies 3x-12y=4$ another method: $\displaystyle y = \frac{x}{4} - \frac{1}{3} = \frac{3x-4}{12}$ $\displaystyle \therefore 12y = 3x-4 \implies 3x-12y=4$
View Tag Cloud